Studi percepatan tanah maksimum wilayah Sumatera Barat dengan metode NGA (Next Generation Attenuation) (Study of the maximum soil acceleration of the West Sumatra region using the NGA (Next Generation Attenuation) method ) - Sandra Gusdalina; - Syafriani; - Ma’muri (Department of Physics – Universitas Negeri Padang UNP, 2018)
West Sumatera is an earthquake prone area because it is in the active subduction zone between the Indo-Australian plate and the Eurasian plate. In addition, West Sumatera is also traversed by the Sumatera fault system, which consists of four active fault segments, namely the Sumpur segments, the Sianok segment, the Sumani segment and the Diffi segment. From every earthquake that occurs in a place will cause a value of ground acceleration. The maximum ground acceleration value can be determined by direct measurement using Accelerograph or by attenuation formulation such as the Fukushima and Tanaka attenuation formulation (1990) and the Patwardhan attenuation formula. The data used in this study is the PGA Accelerograph value recorded in the February 2013-December 2017 period at the Padang Panjang BMKG. The magnitude used is 3.3-6.2SR and its depth is 2-218 km. the calculated PGA value using the attenuation formula will be compared with the PGA value from Accelerograph. Data processing is done by using three sensors namely Sta. sensor Geof. Padang Panjang. Sta. Met. Ketaping and Sta. Mar Teluk Bayur Padang. Based on the three sensors, the PGA value is calculated based on the formulation of Fukushima and Tanaka (1990) and Patwardhan attenuation according to the coordinates of each sensor. After obtaining the PGA value, the calculation of the attenuation formula was compared with the PGA value recorded by Accelerograph. From the three sensors, it was found that the PGA value calculated using the Fukushima and Tanaka formula (1990) approached the PGA value of Accelerograph. So the formulation of Fukushima and Tanaka (1990) is used to find the value of PGA in the West Sumatera region. Based on the formulation of the Fukushima and Tanaka (1990) attenuation, the city or district was obtained. Which has the highest PGA value in Kab. Mentawai Island. This is because the earthquake that occurs has a shallow depth and distance of earthquake sources close to kep regency Mentawai.